THE RELATIONSHIP OF FAMILY ROLES AND ATTITUDES IN CHILD CARE WITH CASES OF CAPUT SUCCEDENEUM IN RSUD LABUANG BAJI, MAKASSAR CITY IN 2018 - Herman Herman (Sekolah Tinggi Pariwisata Mataram, 2020)
Newborns (BBL) are babies who have just undergone the birth process, aged 0-28 days. BBL requires physiological adjustments in the form of maturation, adaptation (adjusting from intrauterine life to extraurine life) and tolerating BBL to live well. The succedeneum head is a banjolan or swelling due to the presence of lymph nodes in the head (at the percentage of the head) that occur in babies born. The purpose of this study was to determine the relationship of family roles and attitudes in the care of children with cases of headache succedeneum. The method used was cross sectional, using the chi square test design. The sample of 34 respondents was chosen by using purposive sampling at RSUD Labuang Baji Makassar. The results of this study showed that respondents with positive succedeneum caput were as many as 88.2% of respondents who played a role and fewer than negative respondents who played no role namely as much as 11.8%. Based on the chi square test, the analysis shows the relationship between family attitudes in child care and the succedeneum caput results obtained by analysis of indigo p = 0.005 <α = 0.005. The conclusion is there is a relationship between the role and attitudes of families with child care cases of succedeneum caput.